FRI0719-HPR AN EVALUATION OF A FIBROMYALGIA EXERCISE PROGRAMME DELIVERED IN THE UNITED KINGDOM NATIONAL HEALTH SERVICE. (June 2019) - Pearson, Jennifer; Lloyd, Michael; Bisset, Michael; Derham, Sandra; Russell, Julie; Palmer, Shea
Abstract : Background: Fibromyalgia (FM) is a complex long-term condition affecting up to 5.4% of the UK population 1 . It is associated with chronic widespread pain, fatigue, stiffness, sleep problems, memory and concentration difficulties, and irritable bowel syndrome 2 . FM guidelines recommend exercise as a core treatment for the management of FM symptoms 3 . Evidence shows exercise interventions are effective for people with FM, reducing pain and improving function and muscle strength 4 . Objectives: This study aimed to evaluate the effectiveness of introducing a FM exercise group programme within a United Kingdom National Health Service hospital setting. Methods: A pre and post evaluation was conducted. People with FM attending a rheumatology therapy department were invited to take part in a FM group exercise programme (60 minutes, once per week, seven weeks). To improve adherence, the exercise programmes were individualised based upon patients' preferences for aerobic or resistance exercise or both. Pre and post Revised Fibromyalgia Impact Questionnaire (FIQR), self-efficacy scale and sit-to-stand in 30 seconds outcome data were collected. Data were analysed using parametric paired samples t-tests and standardised effect size (Cohen's d). Results: A total of n=20 patients completed the exercise programme (n=3 non-completers had higher baseline FIQR scores). Of the 20 completers the mean age was 49.9 years; n=19 were women; n=2 had a concomitant diagnosis of Joint Hypermobility Syndrome and n=1 had Inflammatory Arthritis. The results demonstrated statistically significant improvements across all outcome measures. There were large standardised effect sizes: self-efficacy d=0.93 (95% Confidence Interval (CI) 1.56, 0.26), FIQR d=-1.00 (-0.32, -1.64), sit to stand in 30 seconds d=0.76 (0.07, 0.75). Conclusion: An exercise programme for patients affect by FM can be successfully delivered in a hospital setting. Those who completed the programme saw large improvements in pain, self-efficacy and sit to stand. However, further research is needed to confirm the findings of this uncontrolled study. References: [1] Weir PT, Harlan GA, Nkoy FL, Jones SS, Hegmann KT, Gren LH, Lyon JL. The incidence of fibromyalgia and its associated comorbidities: a population-based retrospective cohort study based on International Classification of Diseases, 9th Revision codes. JCR: Journal of Clinical Rheumatology. 2006Jun1;12(3):124-8. [2] Bennett RM. Clinical manifestations and diagnosis of fibromyalgia. Rheumatic Disease Clinics of North America. 2009May31;35(2):215-32. [3] Macfarlane GJ, Kronisch C, Dean LE, Atzeni F, Häuser W, Fluß E, Choy E, Kosek E, Amris K, Branco J, Dincer F. EULAR revised recommendations for the management of fibromyalgia. Annals of the rheumatic diseases. 2016Jul4:annrheumdis-2016. [4] Busch AJ, Webber SC, Richards RS, Bidonde J, Schachter CL, Schafer LA, Danyliw A, Sawant A, Dal Bello-Haas V, Rader T, Overend TJ. Resistance exercise training for fibromyalgia. Cochrane database of systematic reviews. 2013(12). Disclosure of Interests: None declared